Optimization Of Formula Crackers Enhanced With Kelor (Moringa Oleifera) Leaves Using Mixture Design Method - Iwansyah, Ade Chandra; Herminiati, Ainia; Axxel Faaza Zulkarnain,; Yusep Ikrawan, (Enhanced Knowledge in Sciences and Technology, 2021)
This study aimed to obtain the optimal formulation in the manufacture of moringa crackers using the D-Optimal Mixture Method. The research stages were carried out divided into three stages, including: (1) characterization of moringa leaves powder and crackers; (2) determining the raw material for crackers from cassava starch, mocaf, and wheat flour; (3) optimization of the formula crackers by adding moringa leaves powder using the Mixture Design method. A combination of flour (46.43 %) and moringa powder (4.57 %) resulted in an optimum moringa crackers formulation. This formulation could provide hardness 2470.65 g, fracturabillity 297 mm, moisture 3.58%, ash 3.48%, protein 12.45%, color 4.07, aroma 4.03, taste 3.73, and overall 3.97. The moringa crackers prepared using showed the best solution for this combination of variables with a desirability value of 0.554.